Inefficacy of anti-VEGF therapy reflected in VEGF-mediated photoreceptor degeneration - Xin Xu; Ni Han; Fangkun Zhao; Ruoyue Fan; Qingguo Guo; Xuefei Han; Ying Liu; Guangzuo Luo (Elsevier, 2024)
Retinal neovascularization (RNV) is primarily driven by vascular endothelial growth factor (VEGF). However, current anti-VEGF therapies are limited by short half-lives and repeated injections, which reduce patient quality of life and increase medical risks. Additionally, not all patients benefit from anti-VEGF monotherapy, and some problems, such as unsatisfactory vision recovery, persist after long-term treatment. In this study, we constructed a recombinant adeno-associated virus (AAV), AAV2-SPLTH, which encodes an anti-VEGF antibody similar to bevacizumab, and assessed its effects in a doxycycline-induced Tet-opsin-VEGFA mouse model of RNV. AAV2-SPLTH effectively inhibited retinal leakage, RNV progression, and photoreceptor apoptosis in a Tet-opsin-VEGF mouse model. However, proteomic sequencing showed that AAV2-SPLTH failed to rescue the expression of phototransduction-related genes, which corresponded to reduced photoreceptor cell numbers. This study suggests that anti-VEGF monotherapy can significantly inhibit RNV to some extent but may not be enough to save visual function in the long term.